Retrospective review: single- and multidonor washed microbiota transplantation have equivalent efficacy in the treatment of autism - Ya-Mei Zheng; Meng-Meng Ye; Hong-Ying Zhang; Dan-Ping Luo; Tao Liu; Xing-Xiang He; Xian-Yun Chen; Li-Hao Wu (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAutism spectrum disorder (ASD) is a serious neurodevelopmental disorder with no effective treatment. This study explored the short-term clinical effects of washed microbiota transplantation (WMT) with different numbers of donors on autism.MethodsConsecutive ASD patients treated with two continuous WMT courses from March 2020 to March 2022 at the First Affiliated Hospital of Guangdong Pharmaceutical University were retrospectively assessed. Basic information, aberrant behavior checklist (ABC) scores, childhood autism rating scale (CARS) scores, sleep disturbance scale for children (SDSC) scores, adverse reactions, and feces were collected.ResultsForty-four patients were included (single-donor group: 17 patients; multidonor group: 27 patients). The CARS, ABC and SDSC scores didn’t differ between the two groups before treatment. After two courses, the scores for the 44 patients were lower than those at baseline (P<0.05), with no severe adverse reactions observed. After the first course, the mean ABC (P=0.049) and SDSC (P=0.019) scores were significantly different between the single-donor and multidonor groups, but the difference disappeared after two courses. The alpha-diversity of the faecal flora in the effective-group was greater than that in the ineffective-group (Shannon index P=0.0018). Lactobacillus was the predominant genus in the effective group, whereas Faecalibacterium, Campylobacter, and Sphingomonas were predominant genera in the ineffective group.ConclusionAfter two WMT courses, the symptoms of ASD improved, with good short-term treatment efficacy. The ASD symptom improvement did not differ between the single-donor and multidonor groups. Changes in the alpha-diversity and abundance of the faecal microbiota after WMT may be related to treatment efficacy.